Traditional Ngaben or Crematorium Ngaben? - I Gede Suwindia; Made Ferry Kurniawan (Universitas Pendidikan Ganesha, 2023)
Today, Ngaben as a cremation procession for the Hindu community in Bali is not only in the traditional form, but the cremation procession is also carried out in the crematorium. This transition or process becomes an interesting aspect, when studied sociologically. The purpose of this research is to analyze the background of the change, from the procedure for carrying out the traditional ngaben to the crematorium. ngaben .The method used in this research is quantitative-descriptive, with data collection processes in the form of questionnaires, interviews and observations. The questionnaire was used to determine the percentage of the Balinese Hindu community regarding the existence of traditional ngaben to the crematorium ngaben. Then, interviews were conducted with several respondents, with the aim of knowing the existence of traditional cremation and the transition to the implementation of crematorium cremation. Finally, observations were made with the aim of observing the existence of a crematorium in a traditional village. The recommendation from this study is that the procedure for carrying out cremation, whether carried out traditionally or in a crematorium, is a ceremonial activity that needs to be maintained. The procedure for carrying out the liturgy can be carried out according to the previous pattern, or following the current developments of the times, provided that essentially the meaning and philosophical aspects of this liturgy are not diminished. The change in the procedure for burning corpses in the Hindu community in Bali is caused by various factors, such as efficiency, solidarity and ecology. The two types of cremation, are still practiced by Balinese Hindus today.